If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f = -36x + -1 + 9x Reorder the terms: f = -1 + -36x + 9x Combine like terms: -36x + 9x = -27x f = -1 + -27x Solving f = -1 + -27x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Simplifying f = -1 + -27x
| -2(2c-4)= | | 1.8y=3.8 | | 9x^3/2-18=0 | | 0=x^2+3x+8 | | V/6.3=-7 | | 0=x+3x+8 | | f(x)=(x-4)(x+2) | | 2z^2-21z+3=39 | | (1/7)x=8 | | n=25+0.45n | | R=-30n^2+180n+3360 | | xsquared+15=24 | | (4x^2)-6x+3=0 | | 6(8+x)=48-11x | | 2c-12c= | | 6[2-(-3x-2)]=68x+99 | | 24+6-12x=60 | | -7.3t^2+8.25t+2.1=H | | 13(x-5)=12x-69 | | -88=8(1-4x) | | -7.3t^2+8.25t+2.1=x | | 1.63q=9.73 | | 8(a+7b-5)=8a+56b-72 | | 7=56y | | -7.3t^2+8.25+2.1=x | | 2x-7=2y-13 | | 3x^3y^4+18x^2y^4-6x^2y^4-36xy^4=0 | | 1.7=2.38 | | |z|=-1/5 | | 4a/-8=24 | | 5/8÷15/32 | | Ln*(x-1)-(ln*x)=3+(ln*3) |